2020
DOI: 10.1123/ijspp.2019-0963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Marathon on Skin Temperature Response After a Cold-Stress Test and Its Relationship With Perceptive, Performance, and Oxidative-Stress Biomarkers

Abstract: Context: Although skin-temperature assessment has received much attention in recent years as a possible internal-load measurement, scientific evidence is scarce. Purpose: To analyze baseline skin temperature and its rewarming through means of a cold-stress test before and after performing a marathon and to study the association between skin temperature and internal/external-load measurements. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
2
23
1
1
Order By: Relevance
“…Considering previous reports about the importance of a daily IRT asymmetry assessment in injury prevention [ 17 , 19 , 21 , 22 , 23 ], long-term follow-up studies of athletes using IRT evaluation are encouraged. Finally, based on a recent study [ 44 ], further investigations assessing the skin temperature recovery after a cold stress test could add valuable information to the vascularization status of the region analyzed by infrared thermography.…”
Section: Discussionmentioning
confidence: 99%
“…Considering previous reports about the importance of a daily IRT asymmetry assessment in injury prevention [ 17 , 19 , 21 , 22 , 23 ], long-term follow-up studies of athletes using IRT evaluation are encouraged. Finally, based on a recent study [ 44 ], further investigations assessing the skin temperature recovery after a cold stress test could add valuable information to the vascularization status of the region analyzed by infrared thermography.…”
Section: Discussionmentioning
confidence: 99%
“…Although sCK and sLDH are considered good indicators of muscle damage [ 11 ], other indirect tools have been used to decrease the invasive procedure during blood collection, such as using visual analog scales to measure DOMS [ 12 ]. Although the monitorization of baseline skin temperature (Tsk) using infrared thermography (IRT) was another methodology proposed, the results of the different investigations are contradictory [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Tsk assessment to obtain information about muscle damage is based on its relationship with inflammation and skin blood flow alterations [ 16 , 18 , 19 ]. It was suggested that inflammation resulting from muscle damage could increase muscle temperature and alter Tsk [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations